Penjadwalan Produksi dengan Metode Johnson dan Heuristic untuk Meminimasi Makespan, Total Flow Time, serta Idle Time - Purwatiningsih, Dyah Retno; Khusnita, Hima (Jurnal Teknik Industri, 2001)
Product scheduling system that used by PT Berjaya Sekawanindo for this time, only concidering one purpose criteria for product scheduling is how to finishing all of demand fastest. With only concidering one urpose criteria, cause there are another criterias which neglectfully.